Pembelajaran Kitab Adabul ‘Alim Muta’allim dalam Menanamkan Akhlak Santri Era Milenial - Wulandari, Haviza; Nor Laila, Azzah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The attitudes of today's students have experienced a decline in free association morals such as not respecting teachers and treating them as if they were their friends. Procedures and ethics in seeking knowledge must be applied so as not to damage the world of education. The book Adabul Alim Muta'allim is a guide for overcoming this problem. This research focuses on learning the Book of Adabul Alim Muta'allim using qualitative research methods using data processing techniques, namely interviews, observation, and documentation. The moral values ​​implemented at the Miftahun Najah Islamic Boarding School are sincerity, exemplary, and discipline of students implementing the rules at the Islamic boarding school plays a very important role in instilling morals in students that have been ingrained from an early age. In every process of implementing learning there are inhibiting and supporting factors, the supporting factors are the example of the students, the background of the students in terms of religion and economics, the leadership of the Kyai in the Islamic boarding school which is not under the auspices of the institution, and advice. The inhibiting factors are that educators use monotonous learning methods such as reading books and explaining the contents of the book, students who cannot control their egos or desires, and schools whose environment is dominated by students outside Islamic boarding schools.